2012
DOI: 10.1128/aem.01733-12
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Expansion of the Substrate Range of Methylmalonyl Coenzyme A Synthetase (MatB) of Rhodopseudomonas palustris

Abstract: ABSTRACTMalonyl coenzyme A (malonyl-CoA) and methylmalonyl-CoA are two of the most commonly used extender units for polyketide biosynthesis and are utilized to synthesize a vast array of pharmaceutically relevant products with antibacterial, antiparasitic, anticholesterol, anticancer, antifungal, and immunosuppressive properties. Heterologous hosts used for polyketide production such asEscherichia colioften d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 65 publications
2
48
0
Order By: Relevance
“…Growth of R. palustris on Methyl Malonate Is Not under Acetylation Control-We recently showed that matB is required for photoheterotrophic growth of R. palustris on methyl malonate as a carbon source (36). If RpMatB activity were regulated by acetylation in vivo, we would expect that a deacetylase-deficient strain (⌬srtN ⌬ldaA) would have a growth defect, as is observed during growth on benzoate (Fig.…”
Section: In R Palustris Matb Is Notmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of R. palustris on Methyl Malonate Is Not under Acetylation Control-We recently showed that matB is required for photoheterotrophic growth of R. palustris on methyl malonate as a carbon source (36). If RpMatB activity were regulated by acetylation in vivo, we would expect that a deacetylase-deficient strain (⌬srtN ⌬ldaA) would have a growth defect, as is observed during growth on benzoate (Fig.…”
Section: In R Palustris Matb Is Notmentioning
confidence: 99%
“…2H), it was unclear why this region was important for recognition or acetylation by RpPat. We hypothesized that there was a structural difference between wild-type RpMatB and its chimeras, and we attempted to crystallize both the RpMatB-RpPimA P9 and RpMatB-BxBclM B1 chimeras so that we could compare them with RpMatB and BxBclM, whose structures have been previously published (36,45). Attempts to crystallize either RpPimA or the RpMatB-RpPimA P9 chimera were not successful; therefore, only the RpMatB-BxBclM B1 chimera was pursued.…”
Section: Generation Of Chimeric Variants Of Rpmatb Thatmentioning
confidence: 99%
“…14D). It seems that the shape and electrostatic potential of the chimera loop play important roles, as minor changes in the loop allow an acyl-CoA synthetase to "escape" acetylation by RpPat (214). This indicates that although acetylation motifs may suggest that a protein is controlled by RLA, each substrate should be validated experimentally, as structural elements outside the motif can affect the ability of the acetyltransferase to recognize and acetylate the target.…”
Section: Use Of Protein Chimeras To Probe Gnat Substrate Specificitiesmentioning
confidence: 99%
“…The use of RLA to control acyl-CoA synthetases by acetylation or propionylation is not unique to Gammaproteobacteria, since there is abundant evidence of the same type of control happening in the alphaproteobacterium R. palustris. The common theme here is that RLA helps maintain a balance in the intracellular acetyl-CoA (or propionyl-CoA) pools, while an acyl-CoA synthetase (MatB) that contributes to the succinyl-CoA pool is not under RLA control (28,214). It is possible that acetylation of these AMP-forming acyl-CoA synthetases may control CoA homeostasis by preventing the depletion of CoA or buildup of acetylCoA or propionyl-CoA.…”
Section: Role Of Rla In Maintaining Metabolic Homeostasismentioning
confidence: 99%
See 1 more Smart Citation